Improving the quality of gas supplies to consumers when performing repair work on gas pipelines-branches - I. A. Battalov; Ya. V. Denisova; V. F. Sopin (Омский научный вестник)
Providing consumers with high-quality gas supply services envisages ensuring uninterrupted fuel supply during repair work on gas pipelines - branches. In this regard, the purpose of this study is to consider the organization of the backup fuel supply system for the specified period and develop proposals for its improvement. Achievement of this goal determines the solution of the following tasks: study of regulatory documents in the field of gas supply, consideration of existing options for organizing a backup fuel supply system, development of proposals for their improvement, assessment of the effectiveness of the proposed measures. Based on the results of the study, in order to ensure the provision of high-quality services to consumers for the uninterrupted supply of gas, as an alternative, it is proposed to consider gas supply using mobile automobile gas refuellers and a reducing device. The advantages of using this method and the possible effect of its implementation are noted.